Peningkatan Pengetahuan Posisi Duduk yang Baik Siswa SMP Guna Menghindari Gangguan Muskuloskeletal - Brilian Nur Diansari; Fery Wisnu Saputro; Ikhsanur Rahmad; Muhammad Hidayah Tullah (Kreativasi : Journal of Community Empowerment, 2023)
Sitting position is a part of student’s activities. When students sit in wrong position in the long term that would cause back pain until musculoskeletal disorders. In industrial engineering studied about musculoskeletal disorders that can be seen by pain, stiffness, swelling, redness and changes in joint shape. This community service aims to provide knowledge about good sitting position for Junior High School of 10 Surakarta’s students to avoid musculoskeletal disorders. It is held by face to face. Started with socialization-consultation followed by demonstrations and examples good sitting recommendations. The results showed that all students understood and applied good sitting methods based on the criteria for a good sitting position with a score of more than 77% for each criterion. The details are all of them (100%) already know and apply sitting with an upright body position; 80% have implemented sitting with knees and hips parallel; 77% have implemented sitting with their feet flat on the floor; 90% have implemented sitting by setting a comfortable chair distance and 83% have implemented a reading distance of around 30 cm. It can be concluded that the principles of ergonomics are relevant for improving body posture and avoiding musculoskeletal disorders especially for students. So, it is expected that students consistently sit in a good position.